Carbon dioxide mediates the response to temperature and water activity levels in Aspergillus flavus during infection of maize kernels - Gilbert, Matthew K.; Medina, Angel; Mack, Brian M.; Lebar, Matthew D.; Rodriguez, Alicia; Bhatnagar, Deepak; Magan, Naresh; Obrian, Gregory; Payne, Gary (MDPI, 2017)
Aspergillus flavus is a saprophytic fungus that may colonize several important crops, including cotton, maize, peanuts and tree nuts. Concomitant with A. flavus colonization is its potential to secrete mycotoxins, of which the most prominent is aflatoxin. Temperature, water activity (aw) and carbon dioxide (CO2) are three environmental factors shown to influence the fungus-plant interaction, which are predicted to undergo significant changes in the next century. In this study, we used RNA sequencing to better understand the transcriptomic response of the fungus to aw, temperature, and elevated CO2 levels. We demonstrate that aflatoxin (AFB1) production on maize grain was altered by water availability, temperature and CO2. RNA-Sequencing data indicated that several genes, and in particular those involved in the biosynthesis of secondary metabolites, exhibit different responses to water availability or temperature stress depending on the atmospheric CO2 content. Other gene categories affected by CO2 levels alone (350 ppm vs. 1000 ppm at 30 °C/0.99 aw), included amino acid metabolism and folate biosynthesis. Finally, we identified two gene networks significantly influenced by changes in CO2 levels that contain several genes related to cellular replication and transcription. These results demonstrate that changes in atmospheric CO2 under climate change scenarios greatly influences the response of A. flavus to water and temperature when colonizing maize grain.
Keywords: Aflatoxin; Zea mays; Climate change; Secondary metabolites; RNA-seq